Identification of Functional Gene Modules Associated With STAT-Mediated Antiviral Responses to White Spot Syndrome Virus in Shrimp - Zhu, Guanghui; Li, Shihao; Wu, Jun; Li, Fuhua; Zhao, Xing-Ming (Frontiers in Physiology, 2019)
White spot syndrome virus (WSSV) is one of the major threats to shrimp aquaculture. It has been found that the signal transducer and activator of transcription (STAT) protein plays important roles in the antiviral immunity for shrimp with WSSV infection. However, the mechanism underlying the STAT-mediated antiviral responses in shrimp against WSSV infection is still unclear. In this work, based on the gene expression profiles of shrimps with injection of WSSV and STAT double strand RNA (dsRNA), we construct a gene co-expression network for shrimp and identify the gene modules that are possibly responsible for STAT-mediated antiviral responses. These gene modules are found enriched in regulation of viral process, JAK-STAT cascade and regulation of immune effector process pathways. The gene modules identified here provide insights into the molecular mechanism that underlies the STAT-mediated antiviral response of shrimp against white spot syndrome virus.